ผลของไฮโดรเจนเพอร์ออกไซด์ต่อการขจัดคาร์บอนมอนอกไซด์ ในกระแสเชื้อเพลิงของเซลล์เชื้อเพลิงพีอีเอ็ม - กฤษยาพร ทินกร (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The performance of PEM fuel cell significantly dropped when only a few parts per million of CO containing in fuel stream. The objective of this work was to remove CO from fuel gas stream before delivering to anode electrode by using H[subscript 2]O[subscript 2]. The experiment was performed in a gas reactor which duplicated to anode humidifier unit. The experimental was divided into 4 parts. The reaction between CO and H[subscript 2]O[subscript 2] was studied in the first part. The results were analyzed by FT-IR. It was found that CO[subscript 2] increased with time. The optimum condition for CO removal from fuel stream was next determined in the second part. The results were analyzed by GC. The highest conversion was found when both stainless steel and UV-C light were introduced into the gas reactor which contained H[subscript 2]O[subscript 2] solution at temperature 70 ํC. The average CO conversion could attain at 50% for long time. Effect of CO removal by using H[subscript 2]O[subscript 2] on a performance of anode catalyst was determined in the third part. When applying H[subscript 2]O[subscript 2] solution to the gas reactor CO tolerance of anode catalyst was greater as much as 7 times. A current density after CO removal from fuel gas stream by H[subscript 2]O[subscript 2] was considered in the last part. The results showed current density on impure H[subscript 2] without applying H[subscript 2]O[subscript 2] dropped significantly. On the other hand, when applying H[subscript 2]O[subscript 2] to remove CO from the fuel stream the current density was approaching to that obtained from a case of pure H[subscript 2] fuel gas stream